(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This paper examines large variations in health insurance coverage among Indian states using rich data from the National Family Health Survey (NFHS-5, 2019-21). Using district-level information combined at the state level, we take care to analyze trends in insurance penetration and identify leading and lagging states. The paper compares state-by-state coverage with the country’s all-India average of 41.0% (NFHS-5, 2021) and provides region-specific policy recommendations. Our detailed analysis identifies systemic disparities in access to financial coverage for health, calling attention to the immediate necessity of closing these coverage gaps to promote equitable access to health and attain Universal Health Coverage (UHC) in India.